Pengaruh Media Mobile Learning Berbasis Android “ChemOndro” Pada Model Discovery Learning Terhadap Hasil Belajar Peserta Didik Kelas X SMA Negeri 8 Bone (Studi Pada Materi Pokok Larutan Elektrolit dan Nonelektrolit) - Hidayat, Andi Muhammad Ramadhan; Auliah, Army; Anwar, Muhammad (ChemEdu, 2021)
This study is a quasi-experimental research that aimed to know the effect of mobile learning “ChemOnDro” android based media in discovery learning to student achievement of class X SMA Negeri 8 Bone on subject matter of electrolyte and nonelectrolyte solution. The study design used is "pretest-posttest control group design". The population was all the student of class X MIPA SMA Negeri 8 Bone which is consists of six classes. The sampling technique is random sampling, that the sample are a class X MIPA 1 as an experimental class and class X MIPA 2 as a control class. The independent variable is mobile learning “ChemOnDro” android based media in discovery learning model and discovery learning model without mobile learning “ChemOnDro” android based media, and the dependent variable is student achievement. Result of analysis prerequirement of inferential statistic toward n-gain result, show that the data in experiment class and control class didn’t distributed normaly, but it has homogen varians. The hypothesis test done using with parametric test by Man-Withney with ∝=0.05 was done with zcalculated > ztable (2.07>1,64). Based on these data, it can be concluded that there is an effect of mobile learning “ChemOnDro” android based in discovery learning to student achievement of class X SMA Negeri 8 Bone with subject matter of electrolyte and nonelectrolyte solution.